Evaluation of the Implementation of Postnatal Care Program Paradoxes and Their Impact on the Persistence of Maternal Mortality in Pekalongan Regency - Lusy Supriatinah; Tri Lestari Hadiati; Sumarmo Sumarmo (International Journal of Health and Social Behavior, 2026)
This study aims to analyze the relationship between public policy paradoxes, healthcare service quality, access to and continuity of postnatal care, and maternal mortality in Pekalongan Regency. A mixed-methods approach with a sequential explanatory design was employed, involving 30 respondents for quantitative analysis using Spearman correlation tests and 5 key informants for in-depth interviews. The results indicate that policy paradoxes are strongly correlated with service quality and with access and continuity of care. Service quality also shows a robust correlation with access and continuity. All variables are significantly associated with maternal mortality, with access and continuity of care demonstrating the strongest correlation. Qualitative findings reveal implementation gaps in Ministry of Health Regulation No. 21 of 2021, where postnatal visits are often conducted only 2–3 times instead of the mandated four visits, with 10 out of 13 maternal deaths occurring during the postnatal period. The persistence of maternal mortality is attributed to inconsistent implementation of standard operating procedures, high workload, and socio-cultural factors. The study highlights the need to strengthen supervision, enhance human resource capacity, and promote cross-sectoral collaboration to optimize postnatal care services.